Experiential learning through a peer learning assistant model in STEM. Issue 3 (3rd July 2022) - Gong, Hee Jung; Kwon, Jihye; Brock, Megan
ABSTRACT: Background: Over recent years in colleges and universities, a peer-learning assistant (PLA) model has been introduced into Science, Technology, Engineering, and Mathematics (STEM) classes. Despite the significance of this alternative pedagogical approach in undergraduate education, studies of PLAs' lived experiences of the approach, and hence a deep understanding of the model and its application in higher education, are limited. Purpose: The study sought to gain insight into the learning and teaching experiences of PLAs in an undergraduate STEM class. The PLAs were required to take a pedagogical class as mentors, in addition to having previously undertaken the STEM class themselves. Method: A phenomenological methodology underpinned the study design, supporting the in-depth analysis of rich interview data. Interviews were conducted with five PLAs in STEM majors in a public university in the United States. Interviews were focused on identifying the PLAs' perceptions of their shared experiences, and the knowledge and skills they gained while mentoring peer STEM students and taking a peer-learning pedagogy class. Data were analysed qualitatively, using Kolb's experiential learning as an analytical framework. Findings: The analysis identified how the PLAs experienced the cycle of experiential learning by a) engaging in a STEM class as a student teacher; b) interacting with other PLAs in a pedagogical course; c) developing skills and learning from a pedagogy class; and d) readapting developed peer-teaching abilities and attitudes to a STEM class. Conclusions: Our study contributes to an understanding of PLAs' experiences of the PLA model. The elements we found offer a view into how the PLA students shaped their peer-learning and peer-teaching skills, through their reflections on experiences in both the STEM and pedagogical classes. Through the four elements, students were able to engage in a process that suggested transformative learning. Practical suggestions and scholarly implications for practitioners and researchers are discussed.